Variación de la recarga subterránea : Cuenca arroyo El Pescado (provincia de Buenos Aires) - Laurencena, Patricia Claudia (1999)
This paper deals with the hydrogeological and groundwater characteristics at Arroyo El Pescado basin (Buenos Aires Province). Considering the regional hydrologic behavior, the analysis of water table changes in relation to the different zones in the basin was done. Finally it was established that the relation stored water vs. water excess from hydrologic balance point out the amount of recharge and its influence on the groundwater system.